(untitled) (International Journal of Engineering and Computer Science, 2015)
Digital watermarking has become a promising research area to face the challenges created by the rapid growth in distribution of digital content over the internet. To prevents misuse of this data Digital watermarking techniques are very useful in which a Secret message called as a watermarks which can be a logo or label is embedded into multimedia data imperceptibly which would be then used for various applications like copyright protection, authentication, and tamper detection etc.. Based on the requirement of the application the watermark is extracted or detected by detection algorithm to test condition of the data.